2001
DOI: 10.1039/b007800j
|View full text |Cite
|
Sign up to set email alerts
|

Pd(0)–Cu(I)-catalyzed cross-coupling of alkynylsilanes with triarylantimony(V) diacetates

Abstract: Treatment of alkynylsilanes with triarylantimony diacetates in the presence of Pd 2 (dba) 3 ؒCHCl 3 (5 mol%) and CuI (10 mol%) in CH 3 CN at 50 ЊC for 5 h afforded aryl-substituted alkynes in good yield. Alternatively, direct carbonylative coupling of triarylantimony diacetates with alkynylsilanes was accomplished under atmospheric pressure of carbon monoxide. This coupling was extended to carbonylative cross-coupling of silanes with antimony() compounds. The results are summarized in Scheme 4 and Table 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 17 publications
0
25
1
Order By: Relevance
“…They replaced the commonly used aryl halides in the coupling with organoantimony compounds, namely triarylantimony diacetates (45) [28]. The reaction of 45 with alkynylsilanes (44) palladium(0) complex and copper iodide gave a disubstituted acetylene derivative (46).…”
Section: Sequential Coupling Reactionsmentioning
confidence: 99%
“…They replaced the commonly used aryl halides in the coupling with organoantimony compounds, namely triarylantimony diacetates (45) [28]. The reaction of 45 with alkynylsilanes (44) palladium(0) complex and copper iodide gave a disubstituted acetylene derivative (46).…”
Section: Sequential Coupling Reactionsmentioning
confidence: 99%
“…However, to the best of our knowledge, only a few examples of Pd-catalyzed carbonylative coupling reaction by use of organoantimony compounds have been reported to date. For instance, triarylantimony diacetates were successfully coupled under CO atmosphere with alkynylsilanes [8] to form alkynyl ketones and organostannanes [9] to give aryl-and vinyl ketones. We have also recently demonstrated a new carbonylative cross-coupling reaction between ethynylstibanes and aryl iodides to give ethynyl ketones [10].…”
Section: Introductionmentioning
confidence: 99%
“…Triarylantimony dicarboxylates act as effective arylating agents in Pd-catalyzed C-C(Ar) bond formation reactions such as [28][29][30] 31) and Hiyama-type 32) reactions. Over the past few years, we have also found that they are an efficient aryl donors in base-free Suzuki-type reactions and copper-and base-free Sonogashira-type reactions.…”
Section: The Reaction Of Triarylantimony Diacetates [Ar 3 Sb(oac) 2 ]mentioning
confidence: 99%